Imaging and spectroscopic methods to investigate adult neurogenesis in vivo: New models and new avenues - Just, Nathalie; Chevillard, Pierre-Marie; Migaud, Martine (Frontiers in Neuroscience, 2022)
Adult neurogenesis (AN) can be defined as the birth and development of new neurons at adulthood. Until the 90s, AN was deemed not to happen after birth. Gradually, several groups demonstrated that specific zones of the brain of various species had a neurogenic potential. AN could be the key to treating a large range of neurodegenerative, neuropsychiatric and metabolic diseases, with a better understanding of the mechanisms allowing the regeneration of new neurons. Despite this promising prospect, the existence of AN has not been validated in-vivo in humans and therefore remains controversial. Moreover, the weight of AN-induced plasticity against other mechanisms of brain plasticity is not known adding to the controversy. In the present review, we would like to show that recent technical advances in brain MR imaging methods combined with improved models can resolve the debate.